2019
DOI: 10.1002/poc.3947
|View full text |Cite
|
Sign up to set email alerts
|

Counter‐ion and solvent effects in the C‐ and O‐alkylation of the phenoxide ion with allyl chloride

Abstract: The alkylation reaction of the phenoxide ion with allyl chloride can take place in the oxygen atom or in the carbons of the aromatic ring in the ortho position. Experimental studies have suggested that solvent effects and ion pairing are important for the regioselectivity. In this work, this reaction has been studied by means of theoretical methods using density functional theory, continuum solvation models, and inclusion of some explicit water molecules. It was found that O-alkylation is the only product in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The formation of ion pairs can also change the selectivity. As an example, the C-and O-alkylation of the phenoxide ion depends on the solvent and the formation of ion pairs [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of ion pairs can also change the selectivity. As an example, the C-and O-alkylation of the phenoxide ion depends on the solvent and the formation of ion pairs [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Kornblum and associates investigated the solvent effect on the ratio of O- and C-allylation and benzylation of alkali phenolates and found exclusive O attack in most solvents, except in water and fluorinated alcohols, where O attack is retarded by hydrogen bridging with the consequence that the phenol ethers are accompanied by products of the C attack . Pliego supported this interpretation by quantum chemical calculations …”
Section: Introductionmentioning
confidence: 99%
“…DMF was added as an additive at 60 °C for 14 hr, thus suppressing the Claisen-condensation as a side-reaction according to Kolb and Meier (2012) [9]. It has been found that the addition of 1 eq DMF accelerates the reaction by acting as a good solvation for intermediates and reactants, thus increasing reactivity [15,16]. Dimethyl carbonate was utilized in a large excess of 20 eq.…”
Section: Synthesis Of Malonate Derivative (Dimethyl 2-tetradecylmalonate) (Dmtdm)mentioning
confidence: 99%